167 REGULATION OF PULMONARY VASCULAR SMOOTH MUSCLE CELL PROLIFERATION IN THE OVINE FETUS: ROLE OF CYCLIC GUANOSINE MONOPHOSPHATE-DEPENDENT PROTEIN KINASE. (1st January 2006) - Narasimhan, S. R.; Negash, S.; Raj, J. U.
Abstract : The fetal lung develops in a low oxygen environment with programmed growth of the pulmonary vasculature. To investigate the regulation of proliferation of pulmonary vascular smooth muscle cells (PVSMCs), we studied the effect of hypoxia on near-term ovine fetal PVSMC adhesion, migration, and proliferation. Both arterial (PA) and venous (PV) SMCs were incubated in normoxia (pO2 ≈100 torr) or hypoxia (pO2 ≈30-40 torr) for 24, 48, and 72 h. Cell adhesion to various matrix proteins (collagen I, collagen IV, fibronectin, laminin) was determined by measuring absorbance of a dye staining cell membranes, cell migration was assessed by a wound healing model, and cell proliferation was measured by a cell counting kit. We also measured cGMP-dependent protein kinase (PKG) protein expression by Western blotting. As previously reported, exposure to hypoxia produced a decrease in PKG protein expression in both PA and PV SMC. Hypoxic exposure resulted in a decrease in cell adhesion, an increase in cell migration, and an increase in cell proliferation in both PA and PV SMCs. Inhibition of PKG kinase activity by preincubation with Rp -8-Br-PET-cGMPS (a cyclic guanosine 3′, 5′-cyclic monophosphate analogue) in normoxia decreased cell adhesion in both cell types. We conclude that in hypoxia, inhibition of PKG protein expression and kinase activity promotes PVSMC growth and proliferation by reducing cell adhesion.